Akt2 (Protein Kinase B Beta) Stabilizes ATP7A, a Copper Transporter for Extracellular Superoxide Dismutase, in Vascular Smooth Muscle: Novel Mechanism to Limit Endothelial Dysfunction in Type 2 Diabetes Mellitus. Issue 3 (March 2018) - Sudhahar, Varadarajan; Okur, Mustafa Nazir; Bagi, Zsolt; O'Bryan, John P.; Hay, Nissim; Makino, Ayako; Patel, Vijay S.; Phillips, Shane A.; Stepp, David; Ushio-Fukai, Masuko; Fukai, Tohru
Abstract : Objective—: Copper transporter ATP7A (copper-transporting/ATPase) is required for full activation of SOD3 (extracellular superoxide dismutase), which is secreted from vascular smooth muscle cells (VSMCs) and anchors to endothelial cell surface to preserve endothelial function by scavenging extracellular superoxide. We reported that ATP7A protein expression and SOD3 activity are decreased in insulin-deficient type 1 diabetes mellitus vessels, thereby, inducing superoxide-mediated endothelial dysfunction, which are rescued by insulin treatment. However, it is unknown regarding the mechanism by which insulin increases ATP7A expression in VSMCs and whether ATP7A downregulation is observed in T2DM (type2 diabetes mellitus) mice and human in which insulin–Akt (protein kinase B) pathway is selectively impaired. Approach and Results—: Here we show that ATP7A protein is markedly downregulated in vessels isolated from T2DM patients, as well as those from high-fat diet–induced or db/db T2DM mice. Akt2 (protein kinase B beta) activated by insulin promotes ATP7A stabilization via preventing ubiquitination/degradation as well as translocation to plasma membrane in VSMCs, which contributes to activation of SOD3 that protects against T2DM-induced endothelial dysfunction. Downregulation of ATP7A in T2DM vessels is restored by constitutive active Akt or PTP1B −/− (protein-tyrosine phosphatase 1B-deficient) T2DM mice, which enhance insulin–Akt signaling. Immunoprecipitation, in vitro kinase assay, and mass spectrometry analysis reveal that insulin stimulates Akt2 binding to ATP7A to induce phosphorylation at Ser1424/1463/1466. Furthermore, SOD3 activity is reduced in Akt2 −/− vessels or VSMCs, which is rescued by ATP7A overexpression. Conclusion—: Akt2 plays a critical role in ATP7A protein stabilization and translocation to plasma membrane in VSMCs, which contributes to full activation of vascular SOD3 that protects against endothelial dysfunction in T2DM. Abstract : Supplemental Digital Content is available in the text.